A exposição crônica à fumaça do cigarro resulta em remodelação cardíaca e prejuízo da função ventricular em ratos - Castardeli, Édson [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Campana, Álvaro O. [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2005)
OBJETIVO: Determinar as alterações cardíacas estruturais e funcionais causadas pela exposição à fumaça do cigarro em ratos. MÉTODOS: Os animais foram aleatoriamente distribuídos em dois grupos: fumante (F), composto por 10 animais, expostos à fumaça do cigarro, na taxa de 40 cigarros/dia e controle (C), constituído por 10 animais não submetidos à exposição. Após 4 meses, os animais foram submetidos a estudo morfológico e funcional por meio do ecocardiograma. As variáveis estudadas foram analisadas pelo teste t ou pelo teste de Mann-Whitney. RESULTADOS: Os ratos fumantes apresentaram maior átrio esquerdo (F=4,2± 0,7mm; C=3,5±0,6mm; p<0,05), maiores diâmetros diastólicos (F=7,9±0,7mm; C=7,2±0,5mm; p<0,05) e sistólicos (F=4,1 ±0,5; C=3,4±0,5; p<0,05) do ventrículo esquerdo (VE). O índice de massa do VE foi maior nos animais fumantes (F=1,5 mg/kg± 0,2; C=1,3 mg/kg±0,2; p<0,05), e a fração de ejeção (F=0,85±0,03; C=0,89±0,03; p<0,05) e a fração de encurtamento (F=47,8 %±3,7; C=52,7%±4,6; p<0,05) maiores no grupo controle. Não foram identificadas diferenças nas variáveis de fluxo diastólico (onda E, na onda A e na relação E/A) transmitral. CONCLUSÃO: A exposição crônica à fumaça do cigarro resulta em remodelação cardíaca, com diminuição da capacidade funcional ventricular.

OBJECTIVE: To determine the cardiac structural and functional alterations caused by cigarette smoke exposure in rats. METHODS: The animals were randomly distributed into the following 2 groups: 1) smokers (S), comprising 10 animals exposed to cigarette smoke at a rate of 40 cigarettes/day; and 2) control (C), comprising 10 animals not exposed to cigarette smoke. After 4 months, the animals underwent morphological and functional study with echocardiography. The variables studied were analyzed by use of the t test or the Mann-Whitney test. RESULTS: The smoking rats had a greater left atrium (S=4.2±0.7mm; C=3.5±0.6mm; P<0.05), and greater left ventricular diastolic (S=7.9±0.7mm; C=7.2±0.5mm; P<0.05) and systolic (S=4.1±0.5; C=3.4±0.5; P<0.05) diameters. The left ventricular mass index was greater in the smoking animals (S=1.5mg/kg±0.2; C=1.3mg/kg±0.2; P<0.05), and the ejection fraction (S=0.85±0.03; C=0.89±0.03; P<0.05) and the shortening fraction (S=47.8%±3.7; C=52.7%±4.6; P<0.05) were greater in the control group. No differences were observed in the diastolic transmitral flow variables (E wave, A wave, and E/A ratio). CONCLUSION: Chronic cigarette smoke exposure results in cardiac remodeling with a decrease in ventricular functional capacity.
Chronic cigarette smoke exposure results in cardiac remodeling and impaired ventricular function in rats
Keywords: hipertrofia; função ventricular; dilatação ventricular; hypertrophy; ventricular function; ventricular dilation